2017
DOI: 10.3892/mmr.2017.6912
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of murine and human Treg subsets in inflammatory bowel disease

Abstract: Previous studies have indicated that regulatory T cells serve essential roles in maintaining intestinal homeostasis, however, the role of different Treg subsets in modulating inflammatory bowel disease has still not been addressed clearly. In the present study, the authors measured the percentage of Foxp3+ IL‑10+ TGF‑β+ natural Tregs, Foxp3‑ IL‑10+ TGF‑β‑ induced Tregs, CD127‑ induced Tregs and CD8+ Tregs at different time points in DSS‑induced experimental colitis model in murine lamina propria lymphocytes, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
(21 reference statements)
3
22
0
1
Order By: Relevance
“…Indeed, there is evidence that IL-10 exhibits a suppressive and modulatory action by downregulating the activation of the immune cells and co-stimulatory molecules, thus protecting from immune-related mucosal injury during the chronic stage in IBD. Deficiency in IL-10 receptor [42], as well as changes in the subset and in the number of Treg in colonic mucosa and blood, induce the development of severe IBD in mice and humans [41,43]. As obtained using longer administration periods [25], in the current experiment, the treatment with BC for 7 days reduced the increase of IL-10 gene expression in TNBS-induced colitis in mice.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Indeed, there is evidence that IL-10 exhibits a suppressive and modulatory action by downregulating the activation of the immune cells and co-stimulatory molecules, thus protecting from immune-related mucosal injury during the chronic stage in IBD. Deficiency in IL-10 receptor [42], as well as changes in the subset and in the number of Treg in colonic mucosa and blood, induce the development of severe IBD in mice and humans [41,43]. As obtained using longer administration periods [25], in the current experiment, the treatment with BC for 7 days reduced the increase of IL-10 gene expression in TNBS-induced colitis in mice.…”
Section: Discussionsupporting
confidence: 58%
“…Treg and the products of their secretion, the anti-inflammatory cytokines IL-10 and Transforming Growth Factor-β (TGF-β) may play an essential role in the gastrointestinal homeostasis [10,41]. Indeed, there is evidence that IL-10 exhibits a suppressive and modulatory action by downregulating the activation of the immune cells and co-stimulatory molecules, thus protecting from immune-related mucosal injury during the chronic stage in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The unbalanced cellular immune responses seem to be mainly responsible for the initiation and development of the inflammation in IBD. These adaptive cellular responses involve activation of T helper (Th) lymphocytes and suppression of the activity of T regulatory (Treg) cells . We examined the subtypes of T lymphocytes to investigate whether IL‐35 recombinant protein also acted on T cells to play its regulative role.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the acute IBD model that was used in the present study, no significant changes were found in the expression levels of K Ca 3.1 or HDAC3 in splenic CD4 + CD25 + cells ( Figure S6 ). T reg cells decreased during the active stage of IBD and increased during the remission period at the chronic stage of IBD [ 41 ]. Further studies are needed to elucidate the pathophysiological significance of HDAC3-mediated K Ca 3.1 regulation in the development and function of T reg cells using chronic IBD models.…”
Section: Discussionmentioning
confidence: 99%